2009
DOI: 10.4049/jimmunol.0900400
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Alloantigen-Specific Human T Regulatory Cells by Vasoactive Intestinal Peptide

Abstract: T regulatory cells (Tregs) are instrumental in the maintenance of immunological tolerance. Although Treg-based immunotherapy proved successful in preclinical autoimmunity and transplantation, factors involved in the generation of human Ag-specific Tregs are poorly known. In this study, we show that treatment of human CD4+CD25− T cells with the cytokine-like vasoactive intestinal peptide (VIP) during in vitro stimulation induces an anergic FoxP3+CD4+CD25high T cell subset displaying potent regulatory activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 66 publications
3
50
1
Order By: Relevance
“…This study suggested that alloantigen-specific vasoactive intestinal peptide-generated Tregs could be a valuable tool in therapeutic interventions to promote immunotolerance toward allogeneic grafts [104]. Analogous approaches could be developed for specific autoimmune diseases.…”
Section: Self Antigen-derived Peptidesmentioning
confidence: 93%
See 1 more Smart Citation
“…This study suggested that alloantigen-specific vasoactive intestinal peptide-generated Tregs could be a valuable tool in therapeutic interventions to promote immunotolerance toward allogeneic grafts [104]. Analogous approaches could be developed for specific autoimmune diseases.…”
Section: Self Antigen-derived Peptidesmentioning
confidence: 93%
“…Interestingly, cytokine-like vasoactive intestinal peptide treatment to human CD4 + CD25 -T cells resulted in the induction of an anergic CD4 + CD25 + FoxP3 + T cell subset displaying potent regulatory activities against allospecific effector T cells [104].…”
Section: Self Antigen-derived Peptidesmentioning
confidence: 99%
“…One possible explanation for a low VPAC1:VPAC2 ratio in human T cell leukemia blasts compared to healthy peripheral T cells, might be due to normally low VPAC1: VPAC2 expression during T cell development as human thymocytes were found to express much higher levels of VPAC2 compared to VPAC1 [58] . This altered expression profile in leukemia blasts for the VIP receptor signaling axis could contribute to a growth advantage as VPAC1 is a potent G1/S transition arrestor by blocking the upregulation of several cyclins, while VPAC2 acts as a survival factor of mouse Th2 cells [36,52] . High levels of VIP ligand are also detected in human thymus.…”
Section: Vip Signaling Axis and T Cell Leukemiamentioning
confidence: 99%
“…In early activated T cells (5 h), the cAMP dependent CREM/ICER transcription factor is upregulated, which has been shown to "short-circuit" helix-loop-helix transcription factors that are critical for pro-inflammatory cytokine expression [48] . These microarray observations, we propose, can explain at a molecular level how the VIP signaling axis can act in an anti-inflammatory manner, as well as, induce the differentiation of activated T cells toward different effector phenotypes, including T regulatory cells and Th17 cells [36,49] . Since developing and mature T lymphocytes are heterogeneous cell populations, it will be important to generate the next generation of anti-VIP receptor antibodies capable of detecting protein within these hematopoietic subpopulations to confirm which receptor is evoking VIP-initiated signal transduction and altering metabolic cellular changes.…”
Section: Vip Receptor Expression Profile and Its Transcriptome In T Lmentioning
confidence: 99%
See 1 more Smart Citation